Pengaruh Faktor Internal dan Eksternal Terhadap Return Saham Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Periode 2008–2011 - Erric Wijaya; Tinjung Desy Nursanti (Indonesia Banking School, 2014)
This study aims to look at the impact of internal and external factors to the stock return of food and beverage companies listed in the Indonesia Stock Exchange 2008 to 2011 period. The method used is the regression equation analysis of panel data using a common effect type.The results show that the internal factors such current ratio, debt to equity ratio and return on assets showed a positive and significant influence on the company's stock return of food and beverage industry in the BEI. While external factors namely SBI interest rate and economic growth showed a different result, where the SBI interest rate has a negative and significant relationship to the company's stock return, while economic growth has no significant negative relationship to the stock returns.